2023
DOI: 10.1039/d3ta05220f
|View full text |Cite
|
Sign up to set email alerts
|

Surface engineering of a superamphiphilic, self-growing fibrous Janus membrane prepared from mycelium

Joyce Cavalcante,
Gyorgy Szekely

Abstract: The increasing demand for effective oil–water separation materials has encouraged the exploration of sustainable and ecofriendly solutions. In this study, we investigate the surface engineering of a superamphiphilic, self-growing fibrous...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The achieved superhydrophobic/superoleophilic surfaces could enable efficient separation of oil–water mixtures. 17–21 In 2004, Jiang et al 22 first reported the use of superhydrophobic/superoleophilic porous stainless steel mesh membranes for oil–water separation. Moreover, separation membrane materials exhibiting superhydrophilic/underwater superoleophobic properties have been widely investigated for the treatment of oily wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The achieved superhydrophobic/superoleophilic surfaces could enable efficient separation of oil–water mixtures. 17–21 In 2004, Jiang et al 22 first reported the use of superhydrophobic/superoleophilic porous stainless steel mesh membranes for oil–water separation. Moreover, separation membrane materials exhibiting superhydrophilic/underwater superoleophobic properties have been widely investigated for the treatment of oily wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…36 Natural fibrous membranes and the exploitation of their hydrophilic or hydrophobic nature in various applications are rising. Cavalcante et al demonstrated a new application of membrane contactors for developing superamphiphilic mycelium materials; 37 Chen et al reconstructed eco-friendly disposable tableware based on bamboo fiber separation and its network structure; 38 and Oldal et al used green solvents to prepare inherently sustainable CA nanofibers. 39 Herein, we propose, for the first time, a simple strategy to develop a functional textile based on trilayered porous membranes with unidirectional water transport performance and complete degradation for continuous moisture wicking (Figure 1a).…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, most of the high-performance sorbent materials are not cost-effective for large-scale production, and most of the commercially available sorbents are made from nonrenewable polyurethane foams or polypropylene fibers . Other suggested techniques such as nanofibrous gel composites, fluorinated graphene oxide, nonporous fluorinated polyimides, fluorine-functionalized covalent organic framework, MOF-based porous materials, , poly­( N -isopropylacrylamide) hydrogel, fabric materials, cellulose aerogel, composite membranes, and Janus membranes are used for oil–water separation. Also, phase-selective oleogelators (PSOGs) , are not practically accessible since it is difficult to apply the gelator uniformly and remove the delicate gel-like mass of congealed oil from the surface of sea. Therefore, the development of an efficient and feasible scalable technique to tackle oil spills is urgently needed.…”
Section: Introductionmentioning
confidence: 99%